Rekomendasi Perbaikan Infrastruktur TI SMK Berdasarkan Evaluasi Tingkat Kematangan Framework COBIT 5 - Hendrik Kusbandono; Dwiyono Ariyadi (Journal of Applied Informatics and Computing, 2018)
Starting from 2017, the management policy and education authority of Vocational High School in district region is taken over by the provincial government. In order to distribute the services to Vocational High School in several regions, the provincial government applies data service in online. To support online data service between the provincial education office and the Vocational High School in several regions, it is needed the supports of adequate IT infrastructure. The IT infrastructure components cover human resources and IT assets in form of hardware and software. To discover the maturity level of IT infrastructure in each Vocational High School, it is required analysis of IT human resources capability and IT asset owned. The research method used was COBIT 5 framework with a set of best practices which able to facilitate the management to assess and mitigate risks, as well as provide improvement recommendations. Subdomain focus used for evaluations and recommendations were APO07 and BAI09. The results obtained by capability level of each subdomain is at level 1 namely Performed Process that organization performs a process to achieve the purpose with improvement recommendations to Level 2 namely Managed Process.